The anatomy of regional trade agreements with a services component - Myszkowska, Magdalena (Anatomia regionalnych porozumień handlowych z komponentem usługowym, 2019)
Regional trade agreements (RTAs) have risen in number and reach over the years, including a notable increase in the agreements with services commitments. Of the 293 RTAs WTO-notified and currently in force, 142 have provisions liberalizing trade in goods only, while 151 also cover services commitments. On the basis of the World Trade Organization RTA Database, the paper maps the global landscape of RTAs and draws the main trends and characteristics of RTAs services’ proliferation through quantitative and qualitative categorizations of RTAs. The detailed analysis of the recent proliferation of RTAs points to the differences in the anatomy of agreements with a services component and agreements with a goods component
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 29-40
Keywords: GATS; regional trade agreements; RTA; services; trade in services; WTO; regionalne porozumienia handlowe; usługi; handel usługami; Światowa Organizacja Handlu